Baseline survey of Fish for Livelihoods project Myanmar - Brako Dompreh, Eric; Ali, Syed (2023)
This survey is a baseline of Fish for Livelihoods project. It covered various aspects including production, Better Management Practices, Marketing, Feeds, Income and assets, expenditure, credit and extension, food security, Health and sanitation, and Climate perceptions and adaptation strategies.